استجابة الطلاب على تحسين برنامج تعليم الصرف في الوحدة لمحبي اللغة العربية - Hattab, Muhammad; Muhamad, Sahrul; Arifa, Zakiyah (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
The shortage of time in the class makes learning Arabic not maximum, mainly in the mastery of complex Arabic principles that will take quite a lot of time. Thus, the organization Al-Wihdatu Limuhibbi al-Lughah al-Arabiyyah (Al-Wahyu) presents programmes that focus on the development of the Arabic language, especially in mastering the language. The study aims to describe the student's response to the continous improvement Al-Wahyu-Program in improving the mastery of the Arabic language. The methods used in this research are mixed methods or qualitative and quantitative. Data collection techniques are through Interviews and Questionnaires. The source of the research data is a student of Arabic Language Education of the Islamic State University of Alauddin Makassar. The results of this study show that students give a very positive response to the continued improvement of the Al-Wahyu-Program in Sharaf learning. نقص الوقت في الفصل يجعل تعلم اللغة العربية ليس كاملا في إتقان المبادئ العربية المعقدة التي تستغرق وقتا طويلا. وهكذا، فإن منظمة الوحدة لمحبي اللغة العربية (الوحي) تقدم برامج تركز على تطوير اللغة العربية وخاصة في إتقان قواعد اللغة. وهدف البحث إلى وصف استجابة طلاب على تحسين برنامج تعليم الصرف في الوحدة لمحبي اللغة العربية. ومنهجية البحث المستخدمة هي البحث النوعي والكمي. و تقنيات جمع البيانات من خلال عملية المقابلات والاستبيانات. ومصدر بيانات البحث هو طلاب في قسم تعليم اللغة العربية بجامعة علاء الدين الإسلامية الحكومية مكاسر. أظهرت نتائج هذا البحث أن الطلاب يقدمون استجابة إيجابية جدا لتحسين برنامج الوحي في تعليم الصرف.